AIR FLOW SEPARATION SUPPRESSION STRUCTURE OF MOVING BODY - SAKUMA YUTAKA (2012)
PROBLEM TO BE SOLVED: To provide an air flow separation suppression structure of a moving body that suppresses separation of an air flow from the head of the moving body by a simple structure.SOLUTION: A separation suppression part 6 guides an air flow F, having collided with the vehicle-body end surface 3a of a vehicle 2, to the vehicle-body upper surface 3d of the vehicle 2, thereby suppressing separation of the air flow F from the head of the vehicle 2. When the vehicle 2 travels in the X axis direction, the air flow F, having collided with the vehicle-body end surface 3a, is guided to an inclined surface 8a of a guide part 8 by a curved surface 7a of a guide part 7. Thus, the air flow F is guided from the vehicle-body end surface 3a to the vehicle-body upper surface 3d and the air flow F flows along the surface of the vehicle-body upper surface 3d. As a result, this structure suppresses an increase in the apparent cross-sectional area of the head of the vehicle 2 and reduces a pressure variation occurring when the vehicle 2 runs into a tunnel or the like.